Anesthetic Choice and Management in Cesarean Section for a Patient with Post Laminectomy and Inferior Stabilization: A Case Report - Inggar Nastiti Aifunan; Donni Indra Kusuma (JAI (Jurnal Anestesiologi Indonesia))
Background: Deciding the choice of anesthetic choice and management for a cesarean section is a relatively complex procedure. In this case report we examine a patient undergoing cesarean section who has a significant history of laminectomy with inferior stabilization, the complexities of the patient's conditions may influenced the choice of anesthetic strategy. Case: A 29-year-old female patient undergoing a cesarean section with a complex medical history, including two previous cesarean sections and a laminectomy with inferior stabilization, presenting unique challenges in obstetric and anesthetic care. The patient was admitted to K.M.R.T Wongsonegoro Hospital, Semarang, at 40 weeks of gestation, with symptoms of intense abdominal tightening, active fetal movement, and bloody mucus. Her medical history was further complicated by a laminectomy with inferior stabilization performed in 2019.